Precision medicine for epilepsy: challenges and perspectives for an optimized clinical care pathway - Morita-Sherman, Marcia; Trinka, Eugen; Kwan, Patrick; Ikeda, Akio; Cho, Min; Hampel, Harald (Frontiers in Neurology, 2025)
Epilepsies are a common, but heterogeneous group of brain disorders, characterized by an enduring predisposition to recurrent epileptic seizures. Recognizing epilepsies as a disease spectrum offers compelling opportunities to implement precision medicine in routine care. In this narrative review, we assess the status and development of precision epilepsy, compare its implementation with the advanced model of precision oncology, and discuss strategies to advance the implementation of precision medicine in epilepsy care. We aim to raise awareness about the current state-of-the-art approaches in precision epilepsy, emphasizing their potential to optimize epilepsy care. Rapid technological innovations provide the foundation to improve epilepsy research and management including the establishment of multi-dimensional biomarkers to aid disease subtyping and treatment decision. We also introduce emerging digital health technologies that will transform seizure monitoring and prediction. Advances in data science and artificial intelligence will deepen our knowledge of epilepsies, and may deconstruct and systematize historical, clinical, and descriptive concepts. Following a thorough examination of the current epilepsy landscape – including obstacles against precision medicine implementation and clinical adoption - we envision that the path toward precision epilepsy care lies in studies uncovering the mechanisms underlying systems-biology and neurophysiology-based epileptogenesis using technological innovations, such as genetic testing, fluid indicators, neuroimaging, neurophysiology, and wearable devices. We review the literature based on four core pillars - biomarkers, digital technologies, systems medicine, and data science - to pinpoint the unmet need for epilepsies and thus revolutionize disease management strategies.